Privatization, Investment and Ownership Efficiency - Richard Friberg; Pehr-Johan Norbäck; Lars Persson (Research Institute of Industrial Economics (IFN), 2008)
We provide a model that explains the following empirical observations: i) private ownership is more efficient than public ownership, ii) privatizations are associated with increases in efficiency and iii) the increase in efficiency predates the privatization. The two key mechanisms explaining the results are: (i) a government owner keeping control takes into account the negative effect on employment of investment and (ii) a privatizing government has a stronger incentive to invest than an acquiring firm: the government exploits the fact that investments increase the sales price not only due to the increase in the acquirer's profit, but also due to a reduced profit for the non-acquirer.
Keywords: D44; L13; L33; L40; P31; 330; Privatization; Asset Ownership; Restructuring; Oligopoly; Privatisierung; Unternehmenserfolg; Investition; Eigentümerstruktur; Theorie